Towards predicting the product quality in hot-melt extrusion: Small scale extrusion - Josip Matić; Carolina Alva; Andreas Witschnigg; Simone Eder; Kathrin Reusch; Amrit Paudel; Johannes Khinast (Elsevier, 2020)
In product development, it is crucial to choose the appropriate drug manufacturing route accurately and timely and to ensure that the technique selected is suitable for achieving the desired product quality. Guided by the QbD principles, the pharmaceutical industry is currently transitioning from batch to continuous manufacturing. In this context, process understanding and prediction are becoming even more important. With regard to hot melt extrusion, the process setup, optimization and scale-up in early stages of product development are particularly challenging due to poor process understanding, complex product-process relationship and a small amount of premix available for extensive experimental studies. Hence, automated, quick and reliable process setup and scale-up requires simulation tools that are accurate enough to capture the process and determine the product-process relationships. To this end, the effect of process settings on the degradation of the active pharmaceutical ingredient (API) in a lab-scale Leistritz ZSE12 extruder was investigated. As part of the presented study, the limitations of traditional process analysis using integral process values were investigated, together with the potential that simulations may have in predicting the process performance and the product quality. The results of our investigation indicate that the average melt temperatures and the exposure times in specific zones along the screw configuration correlate well with the API degradation values and can be used as potent process design criteria to simplify the process development.